PERBEDAAN KADAR KOLESTEROL LDL DAN HDL ANTARA WANITA VEGETARIAN TIPE VEGAN DAN NON-VEGAN - Edyanto, Ermia; Puruhita, Niken (Journal of Nutrition College, 2012)
ABSTRACTBackground: Studies which investigated different risk for cardiovascular disease in vegetarian reported that each vegetarian diet type had different lipid serum level. Elevated LDL cholesterol level and reduced HDL cholesterol level are independent risk factors for coronary heart disease. This study was aimed to compare levels on LDL and HDL cholesterol between vegetarian vegan and non-vegan.Methods: Two groups of vegetarian women, 23 people in each group of vegan and non-vegan, participated in this cross-sectional study. The data taken of each subject were nutrient intakes (total fat, PUFA, MUFA, SFA, cholesterol, and total fiber), physical activity, body weight, height, LDL and HDL cholesterol serum levels. Data were analyzed by Shapiro-Wilk test, independent-t test, Mann-Whitney test and ANACOVA test.Results: There were no significant differences on LDL and HDL cholesterol serum levels between vegetarian vegan and non-vegan, both before and after variables i.e age, physical activity, body mass index (BMI), amount of total fat, PUFA, MUFA, SFA, cholesterol, and total fiber adjusted (p > 0,05). LDL cholesterol levels for vegetarian vegan and non-vegan were respectively: 97,8 ± 54,87 mg/dl and 112,6 ± 36,03 mg/dl, while for HDL cholesterol, those levels were 54,9 ± 11,15 mg/dl and 55,2 ± 10,82 mg/dl. In multivariant analysis, the most influential variables on LDL cholesterol serum level were age (p = 0,001) and physical activity (p = 0,010), while for HDL serum cholesterol were BMI (p = 0,010) and total fat (p = 0,012). This study also found the significant difference of BMI between vegetarian vegan and non-vegan (p = 0,011), whose for each of groups’ BMI, were respectively: 20,9 ± 3,08 kg/m2 and 23,5 ± 3,53 kg/m2. Conclusion: LDL and HDL cholesterol serum levels are not different between vegetarian vegan and non-vegan. BMI of both groups is different. Age and physical activity affect on LDL serum cholesterol level, while BMI and total fat affect on HDL serum cholesterol level. LDL cholesterol serum level and BMI in vegetarian vegan  are lower than non-vegan. Key words: Vegetarian diet, vegan, non-vegan, LDL cholesterol, HDL cholesterol